2012
DOI: 10.1016/j.jocn.2011.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of 45 patients with trigeminal neuralgia treated with radiosurgery compared to hypofractionated stereotactic radiotherapy, using a dedicated linear accelerator

Abstract: a b s t r a c tRadiosurgery (RS) and hypofractionated stereotactic radiotherapy (HSRT) were performed in 23 and 22 patients respectively for the treatment of trigeminal neuralgia. RS and HSRT were performed with a dedicated linear accelerator (LINAC): an invasive frame (for RS) or a relocatable stereotactic frame fitted with a thermoplastic mask and bite blocks (HSRT) were used for positioning patients. The RS treatment delivered 40 Gy in a single fraction, or for HSRT, the equivalent radiobiological fractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…In one of the largest series that documents the use of LINAC radiosurgery for the treatment of TN, Smith et al reported that 49% of patients experienced ipsilateral facial numbness [ 29 ]. Frameless hypofractionated radiosurgery has been used with similar findings [ 30 ]. In the only LINAC frameless study published, Chen, et al reported 11% having facial numbness and a recurrence rate of 25% [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one of the largest series that documents the use of LINAC radiosurgery for the treatment of TN, Smith et al reported that 49% of patients experienced ipsilateral facial numbness [ 29 ]. Frameless hypofractionated radiosurgery has been used with similar findings [ 30 ]. In the only LINAC frameless study published, Chen, et al reported 11% having facial numbness and a recurrence rate of 25% [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fraioli et al 36 retrospectively evaluated 23 patients who had undergone single-fraction RS (40 Gy) versus 22 patients who had been treated with hypofractionated stereotactic radiotherapy (HSRT; total dose 72 Gy in 6 fractions), delivered to the retrogasserian cisternal portion of the trigeminal nerve. The mean follow-up was 3.9 years.…”
Section: Single-fraction Versus Hypofractionated Rsmentioning
confidence: 99%
“…As technology evolved more precise linacs were made and special accessories and TPSs for SRS became commercially available . However, at institutions with limited resources the extra effort of commissioning and maintaining any additional system can be prohibitive.…”
Section: Introductionmentioning
confidence: 99%